Eric Mascall and the responsibility of the theologian in England, 1962-1977. Issue 3 (2nd October 2021) - Webster, Peter
ABSTRACT: Eric Mascall was one of the most prominent and prolific theologians in the Church of England in the post-war period. This article examines a series of polemical works, in which Mascall attempted to assess, and largely reject, several trends in liberal theology in the 1960s and 1970s. Mascall detected a systemic crisis in the whole relationship of theology, theologians and the Church, that reached down to the foundations of human knowledge and radiated out to the parishes, via the universities and theological colleges in which their ministers were formed. The article examines his view of the relationship of human nature, grace and the eucharistic Church, and its consequences for the theologian. Mascall's polemics are read, as a group, for what they reveal of his understanding of the responsibility of the theologian, and how far his liberal interlocutors had, he believed, lost sight of the true shape of their vocation.